2020
DOI: 10.1101/2020.05.22.106690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning analysis of the bleomycin-mouse model reveals the compartmental and temporal inflammatory pulmonary fingerprint

Abstract: 30The bleomycin mouse model is the most extensively used animal model to study pulmonary fibrosis. 31 Despite this, the inflammatory cell kinetics and cell compartmentalisation is still incompletely 32 understood. Here we simultaneously analysed 16 inflammatory cell populations in 303 samples and 33 applied advanced data modelling to conclusively detail these kinetics. 34 Three days post-bleomycin, the inflammatory profile was typified by acute innate inflammation, 35 pronounced neutrophilia and loss … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, palbociclib treated mice showed a greater loss of bodyweight compared to mice treated with bleomycin only, suggesting more deleterious effects. This difference was most evident during the acute inflammatory phase of bleomycin treatment around day 7-9 [7], and less pronounced thereafter ( Fig. 1e).…”
Section: To the Editormentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, palbociclib treated mice showed a greater loss of bodyweight compared to mice treated with bleomycin only, suggesting more deleterious effects. This difference was most evident during the acute inflammatory phase of bleomycin treatment around day 7-9 [7], and less pronounced thereafter ( Fig. 1e).…”
Section: To the Editormentioning
confidence: 92%
“…Bleomycin-treated mice were co-treated with palbociclib (PD 0332991, 150 mg/kg/day) in a preventive fashion (Fig. 1a), as described previously [6][7][8].…”
Section: To the Editormentioning
confidence: 99%
“…Fibrosis requires a second phase of pro-fibrotic mediator elaboration, which includes TGFb1 (Chaudhary et al, 2006), a potent inducer of extracellular matrix deposition. Owing to the upregulation of anti-inflammatory factors, acute inflammation resolves by day 14; thereafter many alveoli become nearly obliterated with plugs of connective tissue, and evolution of the inflammatory response after BLM indicates a persistent, adaptive immune presence at 21 days (Bordag et al, 2020). Compared to other models of BLM induced lung injury, subcutaneous injections used in our study induced moderate but diffuse inflammatory infiltrates and lung fibrosis.…”
Section: Discussionmentioning
confidence: 54%
“…Pulmonary fibrosis (PF) is a life-threatening pulmonary disease featuring heterogeneous denudation of alveolar epithelium, fibroblast proliferation (Wynn, 2011), excessive collagen, and matrix deposition in the lung. Current therapy is based on empirical anti-fibrotic agents, which have limited benefits and significant side effects (Borgeson et al, 2011). Though the mechanisms of PF are not fully understood, mitochondrial damage and dysfunction has emerged as a key pathogenic factor in the disease (Rangarajan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To address this need, we undertook preclinical studies using a mouse model of bleomycin-induced pneumonitis. Many pathophysiological changes of COVID-19 lung disease (epithelial cytopathy, endotheliitis, inflammatory infiltrates, surfactant loss) are reproduced in the pneumonitis induced by inhaled bleomycin (20,21). Indeed, single cell sequencing studies of mouse bleomycin (22) and COVID-19 (23,24) pneumonitis have shown pathogenic SPP1 pos macrophage orthologues expressing key inflammatory mediators to be prominent in both conditions, along with profoundly reduced expression of anticoagulant and anti-apoptotic protein S in alveolar macrophages.…”
Section: Introductionmentioning
confidence: 99%